Higher Serum Uric Acid is a Risk Factor of Vertebral Fractures in Postmenopausal Women with Type 2 Diabetes Mellitus - Tanaka, Ken-ichiro; Kanazawa, Ippei; Notsu, Masakazu; Sugimoto, Toshitsugu (Experimental and Clinical Endocrinology & Diabetes, 2020)
Purpose Serum uric acid (UA) level may affect bone metabolism because it has an anti-oxidative effect. However, whether serum UA level is associated with a fracture risk in type 2 diabetes mellitus (T2DM) is unclear. We thus aimed to clarify the association between serum UA and bone parameters in T2DM.Methods We conducted a cross-sectional study to investigate the association of serum UA with bone mineral density (BMD) at lumbar spine (LS) and femoral neck (FN), bone turnover markers such as osteocalcin and urine type I collagen cross-linked N-telopeptide (uNTX), and the prevalence of vertebral fractures (VF) in 356 postmenopausal women and 512 men with T2DM.Results Multiple regression analyses adjusted for age, duration of diabetes, hemoglobin A1c, body mass index and log (serum creatinine) showed that serum UA level was significantly and negatively associated with uNTX in postmenopausal women with T2DM, whereas it was not associated with osteocalcin or BMD at each site. In men, serum UA was not associated with BMD or bone turnover markers. Because postmenopausal women with VF were significantly older and had longer duration of diabetes, higher serum creatinine level and lower BMD than those without it, logistic regression analyses adjusted for these confounding factors were performed. Higher serum UA level was significantly associated with the presence of VF.Conclusions The present study showed that higher serum UA is a risk factor for VF independently of BMD in postmenopausal women with T2DM.
Keywords: uric acid; hyperuricemia; vertebral fracture; bone; diabetes mellitus